2021 American College of Rheumatology/Vasculitis Foundation Guideline for the Management of Kawasaki Disease. Issue 4 (7th March 2022) - Gorelik, Mark; Chung, Sharon A.; Ardalan, Kaveh; Binstadt, Bryce A.; Friedman, Kevin; Hayward, Kristen; Imundo, Lisa F.; Lapidus, Sivia K.; Kim, Susan; Son, Mary Beth; Sule, Sangeeta; Tremoulet, Adriana H.; et al.
Abstract : Objective: To provide evidence‐based recommendations and expert guidance for the management of Kawasaki disease (KD), focusing on clinical scenarios more commonly addressed by rheumatologists. Methods: Sixteen clinical questions regarding diagnostic testing, treatment, and management of KD were developed in the Patient/Population, Intervention, Comparison, and Outcomes (PICO) question format. Systematic literature reviews were conducted for each PICO question. We used the Grading of Recommendations, Assessment, Development and Evaluation method to assess the quality of evidence and formulate recommendations. Each recommendation required consensus from at least 70% of the Voting Panel. Results: We present 1 good practice statement, 11 recommendations, and 1 ungraded position statement to guide the management of KD and clinical scenarios of suspected KD. These recommendations for KD are focused on situations in which input from rheumatologists may be requested by other managing specialists, such as in cases of treatment‐refractory, severe, or complicated KD. The good practice statement affirms that all patients with KD should receive initial treatment with intravenous immunoglobulin (IVIG). In addition, we developed 7 strong and 4 conditional recommendations for the management of KD or suspected KD. Strong recommendations include prompt treatment of incomplete KD, treatment with aspirin, and obtaining an echocardiogram in the setting of unexplained macrophage activation syndrome or shock. Conditional recommendations include use of IVIG with other adjuvant agents for patients with KD and high‐risk features of IVIG resistance and/or coronary artery aneurysms. These recommendations endorse minimizing risk to the patient by using established therapy promptly at disease onset and identifying situations in which adjunctive therapy may be warranted. Conclusion: These recommendations provide guidance regarding diagnostic strategies, use of pharmacologic agents, and use of echocardiography in patients with suspected or confirmed KD.